Intimate partner violence against married and cohabiting women in sub-Saharan Africa: does sexual autonomy matter? - Richard Gyan Aboagye; Louis Kobina Dadzie; Francis Arthur-Holmes; Joshua Okyere; Ebenezer Agbaglo; Bright Opoku Ahinkorah; Abdul-Aziz Seidu (BMC, 2022)
Plain language summary Globally, intimate partner violence is regarded as a public health concern due to its devastating effects on the physical, emotional, and reproductive health of women. This study sought to determine how women's capacity to refuse sex, negotiate for safe sex practices such as insisting on partner to use condom, and feeling justified in asking a partner to use condom is associated with the potential of experiencing violence from an intimate partner. Using data from the demographic and health survey conducted between 2010 and 2019, we found that women who had more capacity to refuse sex, negotiate for safe sex practices such as insisting on partner to use condom, and feeling justified in asking a partner to use condom were more likely to experience violence from their intimate partners after controlling for other factors such as the age of the woman, level of education, marital status, place of residence, economic status, and media exposure. The results highlight the need for sub-Saharan African countries to step up programs that ease up intimate partner violence reporting and access to legal support for those who experience it. Additionally, laws need to be passed and implemented, with law enforcement agencies provided with the necessary resources to reduce intimate partner violence among women with sexual autonomy.